2020
DOI: 10.1126/sciadv.abd1654
|View full text |Cite
|
Sign up to set email alerts
|

Overturning circulation, nutrient limitation, and warming in the Glacial North Pacific

Abstract: Although the Pacific Ocean is a major reservoir of heat and CO2, and thus an important component of the global climate system, its circulation under different climatic conditions is poorly understood. Here, we present evidence that during the Last Glacial Maximum (LGM), the North Pacific was better ventilated at intermediate depths and had surface waters with lower nutrients, higher salinity, and warmer temperatures compared to today. Modeling shows that this pattern is well explained by enhanced Pacific merid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 170 publications
3
47
1
Order By: Relevance
“…Previous studies suggested that North Pacific deep-water could form during the last deglacial abrupt cold events due to increased surface salinity driven by subdued local freshwater flux (Okazaki et al, 2010;Rae et al, 2014Rae et al, , 2020Yu et al, 2020). Precipitation in the North Pacific mid-latitudes is mainly shaped by the storm tracks, the position of which can be affected by the equator-to-pole temperature gradient (Brayshaw et al, 2008;Shaw et al, 2016).…”
Section: Deep-ocean Oxygenation In the Japan Sea Caused By Deep-water Formation In The North Pacificmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that North Pacific deep-water could form during the last deglacial abrupt cold events due to increased surface salinity driven by subdued local freshwater flux (Okazaki et al, 2010;Rae et al, 2014Rae et al, , 2020Yu et al, 2020). Precipitation in the North Pacific mid-latitudes is mainly shaped by the storm tracks, the position of which can be affected by the equator-to-pole temperature gradient (Brayshaw et al, 2008;Shaw et al, 2016).…”
Section: Deep-ocean Oxygenation In the Japan Sea Caused By Deep-water Formation In The North Pacificmentioning
confidence: 99%
“…More saline and oxygen-rich surface water would act directly to erode the halocline and facilitate deep-water formation. Higher salinity in the North Pacific may also be driven by increased delivery of more saline subtropical waters into the North Pacific due to an intensification of the westerly winds in the presence of pronounced cooling in the North Hemisphere (Gray et al, 2018;Rae et al, 2020). The late Miocene global cooling may also have caused enhanced Ekman suction in the North Pacific, which could bring up salt from subsurface waters and lead to increased salinity in surface layer (Gray et al, 2018;Okazaki et al, 2010).…”
Section: Deep-ocean Oxygenation In the Japan Sea Caused By Deep-water Formation In The North Pacificmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently this synchronization was ascribed to the formation of NPIW, which regulated the intermediate‐to‐deep ocean stratification and thus North Pacific deep water upwelling, and further modulated the delivery of nutrient and CO 2 ‐rich deep water to the surface ocean (Gong et al., 2019; Worne et al., 2019). Besides, the NPIW formation could also regulate the vertical convection and preformed nutrient content and the associated net efficiency of the biological pump between surface and subsurface North Pacific, which further controlled the CO 2 outgassing (Gray et al., 2018; Rae et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A manual detailing code installation, basic model configuration, and tutorials covering various aspects of model configuration and experimental design, plus results output and processing, is assigned a DOI: https://doi.org/10.5281/zenodo.4903426 (Ridgwell et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%